Research on the Pathways of Digital Transformation Empowered by Technology for the Foreign Trade Business of Technology Enterprises - He, Limei; Hu, Leqiong (Asia Pacific Economic and Management Review, 2025)
With the rapid advancement of information technology, digital transformation has become an essential path for enterprise survival and development. As a vital force driving socio-economic development, the success or failure of the digital transformation of technology enterprises' foreign trade business not only concerns their own survival and development but also significantly impacts the innovation capability and production efficiency of the entire industry and even society. Therefore, exploring the pathways for technology to empower the digital transformation of foreign trade business in technology enterprises is particularly important. This paper is mainly divided into the following parts: Part I is the introduction, explaining the research background and significance; Part II analyzes the current state of foreign trade business in technology enterprises; Part III discusses the problems existing in the foreign trade business of technology enterprises; Part IV provides countermeasures and suggestions; Part V is the conclusion.